Penerapan Sistem Monitoring Suhu, Kelembaban, dan Amonia dengan Notifikasi pada CV. Berkah Bersama - Ulan Purnama, Mega; Nurjannah (Journal Information Technology Trends (JITRENDS), 2023)
Broiler chickens are a rapidly growing breed, and their growth is influenced by environmental conditions. The poultry house is one of the most crucial aspects of broiler chicken management, particularly the conditions inside the house, such as air temperature, humidity, and ammonia levels. Therefore, it is essential to regularly check the poultry house conditions. In this research, the author developed an embedded system capable of detecting temperature, humidity, and ammonia levels inside the poultry house. The system periodically sends temperature, humidity, and ammonia gas information to the Berkah Bersama information system, and this information is displayed in the form of graphs. Temperature, humidity, and ammonia gas information will be sent via email if the environmental conditions exceed or fall below the threshold. The embedded system was created using a microcontroller, temperature and humidity  sensors (DHT11), and an ammonia level sensor (MQ-135). Arduino serves as the microcontroller, and NodeMCU ESP8266 is used as the communication tool to send poultry house environmental conditions to the Berkah Bersama information system (SIBEBE) and the manager via email. Testing was conducted in two stages: functionality and connectivity. Functionality testing demonstrated that the sensors can produce air temperature, humidity, andammonia level information by comparing them with conventional tools. Connectivity testing proved that the NodeMCU ESP8266 module can send monitoring data every day and under specific conditions.